A call to action for blood flow restriction training in older adults with or susceptible to sarcopenia: A systematic review and meta-analysis - Cahalin, Lawrence P.; Formiga, Magno F.; Anderson, Brady; Cipriano, Gerson; Hernandez, Edgar D.; Owens, Johnny; Hughes, Luke (Frontiers in Physiology, 2022)
Background: The extent to which exercise training with blood flow restriction (BFR) improves functional performance (FP) in people with sarcopenia remains unclear. We performed a comprehensive search of BFR training in subjects with sarcopenia or susceptible to sarcopenia hoping to perform a systematic review and meta-analysis on the effects of BFR on FP in older adults without medical disorders, but with or susceptible to sarcopenia. Methods: PubMed and the Cochrane library were searched through February 2022. Inclusion criteria were: 1) the study examined older adults (>55 years of age) with or susceptible to sarcopenia and free of overt acute or chronic diseases, 2) there was a random allocation of participants to BFR and active control groups, 3) BFR was the sole intervention difference between the groups, and 4) the study provided post-intervention measures of skeletal muscle and physical function which were either the same or comparable to those included in the revised European Working Group on Sarcopenia in Older People (EWGSOP) diagnostic algorithm. Results: No studies of BFR training in individuals with sarcopenia were found and no study included individuals with FP values below the EWGSOP criteria. However, four studies of BFR training in older adults in which FP was examined were found. BFR training significantly improved the timed up and go (MD = −0.46, z = 2.43, p = 0.02), 30-s chair stand (MD = 2.78, z = 3.72, p < 0.001), and knee extension strength (standardized MD = 0.5, z = 2.3, p = 0.02) in older adults. Conclusion: No studies of BFR exercise appear to have been performed in patients with or suspected sarcopenia based on latest diagnostic criteria. Despite the absence of such studies, BFR training was found to significantly improve the TUG, 30-s chair stand, and knee extension strength in older adults. Studies examining the effects of BFR in subjects below EWGSOP cut-off points are needed.